Communication about vaccination: A shared responsibility. Issue 11 (1st November 2016) - Biasio, Luigi R.; Corsello, Giovanni; Costantino, Claudio; Fara, Gaetano M.; Giammanco, Giuseppe; Signorelli, Carlo; Vecchio, Davide; Vitale, Francesco
ABSTRACT: Vaccine hesitancy is an important issue to be addressed, due to the risk of decrease of vaccination coverage and consequent control of preventable diseases. While it is not considered a specific determinant, poor or inadequate communication can contribute to vaccine hesitancy and negatively influence vaccination uptake. As a contribution to the ongoing discussion regarding this theme and in the perspective of the implementation of the upcoming national vaccination plan in Italy, the Erice Declaration was drafted by experts in the field of immunization following a 5-day residential, independent workshop regarding communication topics in vaccinology. The aim of the current letter is to present to the broader international audience such a contribution, proposing the identification of the main actions that should be taken into account and prioritized in order to improve communication in the domain of vaccination.